FREQUENCY OF UTERINE CURETTAGE AS A RISK FACTOR AMONG PATIENTS WITH PLACENTA PREVIA PRESENTING AT TERTIARY CARE HOSPITAL - GUL, F; AFTAB , A; AFTAB , M; AJMAL , H; SARWAR , S (Biological and Clinical Sciences Research Journal, 2024)
Placenta previa is the placenta lying entirely or in part in the lower uterine segment. Its incidence is about 0.28–2%. In local studies, a frequency of 0.51–3.5% has been reported. Advancing maternal age, multiparity, previous cesarean sections, miscarriages, uterine curettage cocaine use, smoking, and previous history of placenta previa have all been attributed as risk factors for placenta previa. Objective: To determine the frequency of uterine curettage leading to placenta previa among women presenting to tertiary care hospitals. Methods: This Descriptive cross-sectional study was conducted at the Department of Gynaecology and Obstetrics, Lady Reading Hospital Peshawar from 2/10/2020 to 2/4/2021. In this study, a total of 136 patients were observed. History was taken from the patient (bleeding, pain in abdomen to exclude other causes). Placenta previa was defined as placenta covering or reaching within 2 cm of internal or detected by the last trans-abdominal ultrasonography before delivery. Results: Our study shows that among 136 women mean age was 34 years with SD ± 8.91. 30(22%) patients were primi para while 106(78%) patients were multi para. 27(20%) patients were primi gravida while 109(80%) patients were multi gravida. More than 29(21%) patients had uterine curettage while 107(79%) patients didn’t have uterine curettage. Conclusion: Our study concludes that the frequency of uterine curettage in patients presented with Placenta previa was 21% in our setup.